Contextualizing LGB Youth's Experiences With Victimization and Risky Behaviors: A Qualitative Approach to General Strain Theory. (October 2019) - Button, Deeanna M.
This study uses 20 in-depth interviews with lesbian, gay, and bisexual (LGB) young adults aged 18 to 25 years to integrate theoretical constructs from the sociology of sexuality with Agnew's general strain theory (GST). This approach provides theoretical context to LGB youth's experiences with victimization and risky behaviors. The use of qualitative data provides a deeper understanding of LGB youth's experiences with heteronormativity, heterosexism, and homophobia, and how these structural-level processes shape interactional- and individual-level experiences. Integrating sexuality research and GST helps clarify interconnected processes that occur at multiple levels of social life, providing a more complete picture of LGB experiences.